Binary Targeting of siRNA to Hematologic Cancer Cells In Vivo Using Layer‐by‐Layer Nanoparticles. (27th March 2019) - Choi, Ki Young; Correa, Santiago; Min, Jouha; Li, Jiahe; Roy, Sweta; Laccetti, Kristiana H.; Dreaden, Erik; Kong, Stephanie; Heo, Roun; Roh, Young Hoon; Lawson, Edward C.; Palmer, Peter A.; et al.
Abstract: Using siRNA therapeutics to treat hematologic malignancies has been unsuccessful because blood cancer cells exhibit remarkable resistance to standard transfection methods. Herein, the successful delivery of siRNA therapeutics with a dual‐targeted, layer‐by‐layer nanoparticle (LbL‐NP) is reported. The LbL‐NP protects siRNA from nucleases in the bloodstream by embedding it within polyelectrolyte layers that coat a polymeric core. The outermost layer consists of hyaluronic acid (a CD44‐ligand) covalently conjugated to CD20 antibodies. The CD20/CD44 dual‐targeting outer layer provides precise binding to blood cancer cells, followed by receptor‐mediated endocytosis of the LbL‐NP. This siRNA delivery platform is used to silence B‐cell lymphoma 2 (BCL‐2), a pro‐survival protein, in vitro and in vivo. The dual‐targeting approach significantly enhances internalization of BCL‐2 siRNA in lymphoma and leukemia cells, which leads to significant downregulation of BCL‐2 expression. Systemic administration of the dual‐targeted, siRNA‐loaded nanoparticle induces apoptosis and hampers proliferation of blood cancer cells, both in cell culture and in orthotopic non‐Hodgkin's lymphoma animal models. These results provide the basis for approaches to targeting blood‐borne cancers and other diseases and suggest that LbL nanoassemblies are a promising approach for delivering therapeutic siRNA to hematopoetic cell types that are known to evade transfection by other means. Abstract : This work demonstrates BCL‐2‐targeted precision siRNA therapeutics based on a CD20/CD44 dual‐targeted layer‐by‐layer nanoparticle to regulate BCL‐2 expression in hematologic malignancies. The binary targeting RNAi approach leads to considerable downregulation of BCL‐2 expression, and induces apoptosis of the blood cancer cells in culture and in orthotopic blood cancer animal models.